Adaptive Apparel Design - McKinney, Ellen; Eike, Rachel (Open textbook library., 2023)
This instructional text and designer resources have been prepared to support those learning about adaptive apparel design. The text is easy for students, scholars, and designers to use, and is organized around the apparel design process: research, sketching, developing a sample notebook, mood or inspiration board, pattern work, first sample, and the completed ensemble. Users can read from beginning to end or jump into resources related to their current phase of design.